2014
DOI: 10.1038/bjc.2014.161
|View full text |Cite
|
Sign up to set email alerts
|

The intratumoural subsite and relation of CD8+ and FOXP3+ T lymphocytes in colorectal cancer provide important prognostic clues

Abstract: Background:To find improved tools for prognostic evaluation in patients with colorectal cancer (CRC), we have analysed how infiltration of cytotoxic T lymphocytes (CD8+) and regulatory T lymphocytes (FoxP3+) correlates to prognosis, not only according to quantity and relation, but also to subsite within tumours of different molecular characteristics (microsatellite instability and CpG island methylator phenotype status).Methods:CD8 and FOXP3 expression was evaluated by immunohistochemistry in 426 archival tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
124
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(135 citation statements)
references
References 37 publications
10
124
1
Order By: Relevance
“…2). The majority support a positive impact on prognosis associated with extensive memory T-cell infiltration in the same cancers we discussed earlier, eg, CRC (Anitei et al, 2014;Boissi ere-Michot et al, 2014;Correale et al, 2012;Kim, Bae, et al, 2015;Ling et al, 2014;Ong et al, 2015;Shinto et al, 2014), bladder (Ingels et al, 2014), breast de Kruijf et al, 2013;García-Martínez et al, 2014;Kim et al, 2013;Mohammed et al, 2013;Park et al, 2012;Rathore et al, 2014;Seo et al, 2013;West et al, 2013), Merkel cell carcinoma (Paulson et al, 2014), glioma (Han et al, 2014), pancreatic (Ino et al, 2013;Tang et al, 2014), head and neck (Balermpas et al, 2014;Czystowska et al, 2013;Millrud et al, 2012;Wallis et al, 2015), cervical (Origoni et al, 2013), NSCLC Hald et al, 2013), gastric Feichtenbeiner et al, 2014;Kim et al, 2014), ovarian (Bachmayr-Heyda et al, 2013;Nielsen et al, 2012;Preston et al, 2013), and HCC (Cariani et al, 2012;Chen et al, 2012;Guo et al, 2007;Huang et al, 2012) (Table 1 and Fig. 2).…”
Section: Role Of T Cellssupporting
confidence: 65%
“…2). The majority support a positive impact on prognosis associated with extensive memory T-cell infiltration in the same cancers we discussed earlier, eg, CRC (Anitei et al, 2014;Boissi ere-Michot et al, 2014;Correale et al, 2012;Kim, Bae, et al, 2015;Ling et al, 2014;Ong et al, 2015;Shinto et al, 2014), bladder (Ingels et al, 2014), breast de Kruijf et al, 2013;García-Martínez et al, 2014;Kim et al, 2013;Mohammed et al, 2013;Park et al, 2012;Rathore et al, 2014;Seo et al, 2013;West et al, 2013), Merkel cell carcinoma (Paulson et al, 2014), glioma (Han et al, 2014), pancreatic (Ino et al, 2013;Tang et al, 2014), head and neck (Balermpas et al, 2014;Czystowska et al, 2013;Millrud et al, 2012;Wallis et al, 2015), cervical (Origoni et al, 2013), NSCLC Hald et al, 2013), gastric Feichtenbeiner et al, 2014;Kim et al, 2014), ovarian (Bachmayr-Heyda et al, 2013;Nielsen et al, 2012;Preston et al, 2013), and HCC (Cariani et al, 2012;Chen et al, 2012;Guo et al, 2007;Huang et al, 2012) (Table 1 and Fig. 2).…”
Section: Role Of T Cellssupporting
confidence: 65%
“…In addition, a high concentration of local tumor-infiltrating Tregs is the most crucial factor affecting the prognosis of patients with colon cancer [25–27]. Thus, reducing the number of local tumor-infiltrating Tregs may be of more clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Ling's group reported that a high infiltration rate of FOXP3(?) cells at the tumor invasion front pointed to improved prognosis [21]. Thus, FOXP3(?…”
Section: Discussionmentioning
confidence: 99%